2021
DOI: 10.3390/agronomy11101935
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Agriculture through Industry 4.0

Abstract: Industry 4.0 is currently considered the structural implementation of networked and cooperative digitalisation and the next step in technological and social development. The aim of this paper is to examine how these structures are also suitable for agriculture and whether there are already approaches to this. Therefore, the main aspects of Industry 4.0 will be analysed and compared with agricultural examples from arable farming and livestock farming. The study shows that the approaches of Industry 4.0 are also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 24 publications
0
12
0
4
Order By: Relevance
“…It stems from the role of drones being perceptive and informed about workers' desires and aiding in the decision-making process to address them (Nahavandi, 2019). Several studies have examined the role of I4.0 in tackling workers' health and safety challenges (Trivelli et al, 2019;Bernhardt et al, 2021). However, these studies consider combining manual and automotive processes in addressing challenges.…”
Section: 42mentioning
confidence: 99%
“…It stems from the role of drones being perceptive and informed about workers' desires and aiding in the decision-making process to address them (Nahavandi, 2019). Several studies have examined the role of I4.0 in tackling workers' health and safety challenges (Trivelli et al, 2019;Bernhardt et al, 2021). However, these studies consider combining manual and automotive processes in addressing challenges.…”
Section: 42mentioning
confidence: 99%
“…Many studies reported the benefits of optical sensing and computer vision technologies, such as hyperspectral imaging (HSI) and spectroscopic techniques and, accurate and non‐destructive optical sensing technologies that have been used for the assessment of egg freshness (Giunchi et al., 2008; Karoui et al., 2006a; Liu et al., 2020), gender (Corion et al., 2022; Khaliduzzaman et al., 2019; Rahman et al., 2021a), fertility detection (Adegbenjo et al., 2020; Liu & Ngadi, 2013; Smith et al., 2008), size (Narushin et al., 2004; Suktanarak & Teerachaichayut, 2017), gas composition (Zhang et al., 2022a), proximate composition (Zhao et al., 2018), and fabrication (Chen et al., 2019; Joshi et al., 2022). Although several studies have been published on the use of I4.0 technologies in agriculture (Araújo et al., 2021; Bernhardt et al., 2021; Liu et al, 2021; Patil & Shekhawati, 2019), the food and beverage industry (Akyazi et al., 2020; Demir & Dincer, 2020; Konur et al., 2021; Luque et al, 2017), the meat industry (Barbut, 2020; Echegaray et al., 2022; Kamruzzaman, 2023), supply chains (Ghadge et al., 2020; Mukherjee et al, 2021), resources nexus (David et al., 2022), and traceability (Hassoun et al., 2022c, 2023c), no review has been published on I4.0 applications for the egg industry. Therefore, this review article has focused on those I4.0 technologies for which contemporary research exists related to the egg industry.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, hydroponic cultivation is done conventionally, with manual system operation, and some of them have implemented simple automation technology with a timer-based automation system. There are still a few who develop smart and precise farming systems that collaborate with automation technology and cyber technologies such as the Internet of Things (IoT) [8] [9] [10] [11]. Therefore, there are still many research and development topics that can be done to improve the quality of hydroponic cultivation.…”
Section: Introductionmentioning
confidence: 99%